2004
DOI: 10.1016/j.jctb.2003.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Weakly distance-regular digraphs

Abstract: We introduce the concept of weakly distance-regular digraph and study some of its basic properties. In particular, the (standard) distance-regular digraphs, introduced by Damerell, turn out to be those weakly distance-regular digraphs which have a normal adjacency matrix. As happens in the case of distance-regular graphs, the study is greatly facilitated by a family of orthogonal polynomials called the distance polynomials. For instance, these polynomials are used to derive the spectrum of a weakly distance-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Then, G is a weakly distance‐regular digraph (according to Comellas et al. ) with distance polynomials p0=1,p1=x,p2=x21,p3=1dx3x,and Hoffman polynomial 0trueH=i=03pi=1d(x3x)+x2+x, as shown in .…”
Section: Mixed Bipartite Moore Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, G is a weakly distance‐regular digraph (according to Comellas et al. ) with distance polynomials p0=1,p1=x,p2=x21,p3=1dx3x,and Hoffman polynomial 0trueH=i=03pi=1d(x3x)+x2+x, as shown in .…”
Section: Mixed Bipartite Moore Graphsmentioning
confidence: 99%
“…■ Moreover, the minimum polynomial of is ( ) = 4 − 2 2 . Then, is a weakly distance-regular digraph (according to Comellas et al [4]) with distance polynomials 0 = 1, 1 = , 2 = 2 − 1, 3 = 1 3 − , and Hoffman polynomial = ∑ 3 =0 = 1 ( 3 − ) + 2 + , as shown in (19). For some other values of the diameter, we also have some families of mixed graphs that are asymptotically dense.…”
Section: The Case Of Diameter Threementioning
confidence: 99%
“…If we replace Γ + 1 (v) by Γ − 1 (v), in the definition of distance-regularity, we get a new family of digraphs called "weakly distance-regular digraphs". This concept was introduced by F. Comellas et al [9], as a generalization of distance-regular digraphs. In fact, distanceregular digraphs are precisely weakly distance-regular digraphs with normal adjacency matrices (a matrix A is normal if AA t = A t A, where A t is the transpose of A).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, distance-regular digraphs are normal weakly distance-regular digraphs. Also, in [6] it has been shown that a digraph Γ of diameter D is weakly distance-regular if, for each nonnegative integer ℓ ≤ D, the number a ℓ uv of walks of length ℓ from a vertex u to a vertex v only depends on their distance ∂(u, v).…”
Section: Introductionmentioning
confidence: 99%